Mathematical Model of Cancer with Ordinary Differential Equations - Wahbi, Hagir; Ahmed, Ehssan; Abalgaduir, Alaa; Alshammari, Fahdah (Contemporary Mathematics, 2024)
The cancer cell starts dividing, infiltrating neighboring tissues and traveling throughout the lymphatic system. While there are ways to stop the spread of disease or get rid of infected cells, most of the approaches are unable to identify the early warning indicators of such an occurrence. Using diverse types of differential equations, especially ordinary differential equations (ODEs), is a helpful catalyst that experts employ. Using differential equations, researching resistance to chemotherapy, forecasting potential treatment failure, or evaluating the result and prognosis following various forms of therapy. Living things always include cancer cells, but a biological regulatory system keeps them from spreading to a dangerous degree (think overpopulation vs. natural resources). Therefore, the most efficient method of determining when to effectively intervene with the tumor growth is to use the cytokinetic method of quantitatively assessing the cancer cells’ progression. Cancer Metabolism: One of the main characteristics of cancer is metabolic reprogramming, in which the metabolism of cancer cells is changed to fuel their explosive growth and multiplication. New models of cancer metabolism investigate the roles that dysregulated metabolic pathways play in the genesis and spread of tumors, providing prospective avenues for therapeutic intervention. The mathematical models of tumor growth modeling of ordinary differential equations (ODEs cancer). The tumor grows voraciously, and the scientists and mathematicians who tried to have a better understanding grow. The study of such treatments on models of tumor growth leads to one or more ODEs. Which gives some ideas on the relation between equations and tumor growth in cancer cells introduce ODEs to provide mathematical models of tumor growth. The dynamics of tumor cells and their growths through clinical, experimental, and theoretical approaches, new ideas for different cancer therapies are developed with the goal of controlling and reducing the death rate for earlier diagnosis. The kinetics of tumor cell proliferation and its treatment approach were covered in this research. In order to comprehend the proliferation of tumor cells, we expanded the study and xamined a feew basic mathematical models.